Pemberdayaan Petani Muda melalui Media Sosial dalam Pengembangan Pertanian Berkelanjutan - Cherlina Helena Purnamasari Panjaitan; Candra Supriadi; Wilda Manafe (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
Youth empowerment provides a strategic foundation for advancing agricultural regeneration and hastening the adoption of sustainable farming practices. This community engagement program adopted digital-based training and mentoring, using social media as a medium for education, promotion, and collaborative networking amongst young farmers. The activities were conducted through on-site workshops, followed by online mentoring on content creation, digital communication strategies, and social media account management. Assessment was performed by pre- and post-tests, observation of digital outputs, and group discussions. The results clearly show a significant enhancement in digital literacy, content production skills, and online engagement, with wider dissemination of farming practices and increased adoption of environmentally friendly cultivation methods. Social media was used not only as a marketing platform but also as a tool for knowledge transfer and capacity building. These findings show that tdigital mentoring is an effective way of ensure the sustainability of agricultural transformation among young farmers.